Efektifitas Program BMT NU dalam Meningkatkan Ekonomi Masyarakat - Abdul Wasik (UNIVERSITAS BONDOWOSO, 2021)
Starting from the message of the late KHR. As'ad Syamsul Arifin Caretaker of the Sukorejo Islamic Boarding School. There are three things that students and alumni must do, namely: 1) Serving on education and teaching, 2) fighting for NU organizations, and 3) taking part in thinking about the people's economy. On September 13, 2018, Wonosari Branch BMT NU was launched and launched. The purpose of the BMT NU Louncing is at MWC NU Kec. Wonosari is as follows: first, Increasing the professionalism and understanding of NU citizens in the field of improving the economy of the community by avoiding things that are still unclear in terms of the obvious things halalal thoyyiban; Secondly, to provide a place for the NU community to be more creative and excel in the development of economic activities, whether saving, loans or otherwise based on Islamic sharia in the Kaffah, Third, as community partners in banking problems to help increase business and capital in nature. - Helping